Deep Learning Models for Medical Imaging - Santosh, K. C; Das, Nibaran; Ghosh, Swarnendu (Primers in Biomedical Imaging Devices and Systems, 2021)
Deep Learning Models for Medical Imaging explains the concepts of Deep Learning (DL) and its importance in medical imaging and/or healthcare using two different case studies: a) cytology image analysis and b) coronavirus (COVID-19) prediction, screening, and decision-making, using publicly available datasets in their respective experiments.